POTENTIAL USES FOR Araucaria angustifolia UNDEVELOPED SEEDS - Arantes, Matheus S. T.; Andrade, Dayanne R. M.; Carneiro, Giovanna B. K.; Magalhães, Washington L. E.; da Silva, Vitor R.; Helm, Cristiane V. (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2025)
Undeveloped pinhão seeds (Falhas de Pinhão, FP) are potential by-products on the exploitation of pine cones of Araucaria angustifolia, and this material has no use and little academical research available. In this work, its chemical characterization was conducted, and new uses for this material were proposed, with focus on the potential for the food, cosmetics, energy, and nano-technological areas. The results indicate FP as potential dietary fibers supplement for the application in the food industry. FP can be utilized on the obtention of extracts for the application as source of phenolic compounds and sugars. The high calorific value and low ash content on FP indicates its potential on the energy generation. Yet, other applications were tested, such as the obtention of briquettes, and cellulose-based nanosuspensions and films.